Investigation of Biology Students' Cognitive Structure Ability Regarding the Central Dogma of Molecular Biology - Sutrisno, Sutrisno; Mustofa, Romy Faisal (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
The purpose of this study was to improve biology learning outcomes in genetic material for class XII-MIPA 8 students of SMAN 1 Tasikmalaya in the 2022/2023 academic year. The model is the media image. The subjects of this classroom action research were class XII.MIPA 8 students of SMAN 1 Tasikmalaya. The number of students is 35 people, 14 boys and 21 girls. This classroom behavior study was conducted in the 2022-2023 school year. This classroom action research was conducted for three months in odd semesters starting from October to December 2022. The research methodology for this classroom action research was carried out in two cycles, each cycle consisting of two meetings. Each cycle consists of planning, implementing, observing and reflecting. The research process consisted of Preliminary Research, Cycle 1 Planning, Cycle 1 Action Implementation, Cycle 1 Observation, Cycle 1 Reflection, Cycle 2 Planning, Cycle 2 Action Implementation, Cycle 2 Observation, and Cycle 2 Consists of reflection. The data collection technique is to collect test scores using tests (written tests) given at the end of each lesson in each cycle. Observational data is made by observing student activities during the learning process. Data analysis was performed using percentage statistics. The results showed that the students' learning outcomes increased from 40 before learning to 70 in cycle 1 and 85 in cycle 2. Student learning activities increased from the category of 'Enough' to 'Good' and from 'Good' to 'Very Good'. The application of media images can increase the activity and learning outcomes of biology in the genetic material for class XII.MIPA 8 SMAN 1 Tasikmalaya Academic Year 2022/2023. DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27120